Fenomena Recall Sunarwi (Studi Analisis Pergantian Antar Waktu DPRD Kabupaten Pati Pasca Pemilihan Bupati dan Wakil Bupati Pati tahun 2011) - Hakim Alif Nugroho; Susilo Utomo; Sulistyowati . (Journal of Politic and Government Studies, 2015)
AbstractRecall is one of institutionalization forms of political party as an existence, supervision and control from a party to its members. The implementation will be executed by a political party against its member for violating the provisions of law and dismissal by the political party. Sunarwi in carrying out his duty has clearly been against his political party instructions. His resistance was performed when his political party mandate wasn’t handed to him in the election process of Regent and Vice Regent of Pati region 2011. PDI Perjuangan as his party has suspended the management of DPC PDI PerjuanganPati and has recalling Sunarwi trough the PDI Perjuangan fraction in DPRD Pati. This research holds a purpose to describe and analyze the recall process that has been performed by PDI Perjuangan to Sunarwi as a member of DPRD Pati 2009-2014. The method used in this research is qualitative which is descriptive analytics kind of research. The main source of the data will be obtained through interview with respondents and another data will be obtained from reports and books. Data that has been earned will be analyzed so does the field-gathered information, they will be evaluated and deduced to attain the Sunarwi recall process. Basically every Parliament members in carrying out their duties will be using the representation principle while Sunarwi is the representative of the people who use the delegate principle on legislative elections. But when he became a Member of Parliament, he is using the trustee principle. It can be seen when the recall process is carried out by the political parties supporting him. The clear mechanism is; political party will send a letter to the Chairman of Parliament. But once in Parliament, the Parliament Leader as the actor who supposed to do follow up with Bamus and Paripurna to approve the recall as the next step never conduct the action instead. It makes the Commission (KPU) as the subsequent party is unable to submit and verify the replacement name in the recall process. Not far different from the Regent (Bupati) who is supposed to submit and approve such recall to the Governor; he is unable to do his duty either, even though the role of Chairman of Parliament and the Regent in this recall process is only a procedural formality. It means political party which is the element of the people who had elected him formally through elections has been ignored in the recall process. So it reinforces the reason that Sunarwi is representative of the people who use trustee principle and he is different with the other representatives who use the delegate principle. Keywords: Recall, DPRD (House of Representatives), Political Party, Representative